Blockchain-Based Land Registration System: A Conceptual Framework - Muhammad Irfan Khalid; Jawaid Iqbal; Ahmad Alturki; Saddam Hussain; Amerah Alabrah; Syed Sajid Ullah (Applied Bionics and Biomechanics)
Land registration authorities are frequently held accountable for the alleged mismanagement and manipulation of land records in various countries. Pakistan’s property records are especially vulnerable to falsification and corruption because of the country’s poverty. Different parties therefore claim varying degrees of authority over a specific piece of land. Given the fact that this data has been consolidated, it has become significantly more vulnerable to security threats. The goal of decentralized system research has been to increase the reliability of these systems. In order to fix the flaws of centralized systems, blockchain-based decentralized systems are currently in development. By using significant land record registration models as the basis for this research, we hope to create a proof-of-concept system or framework for future use. Pakistan’s land registration agency will benefit from our proposed conceptual framework. For the Pakistani government to implement a decentralized land record registry system, we propose a conceptual framework that outlines the essential components.